2018
DOI: 10.1002/cta.2572
|View full text |Cite
|
Sign up to set email alerts
|

Secure color image encryption algorithm based on chaotic signals and its FPGA realization

Abstract: In this paper, we designed a three-dimensional chaotic system (3D chaotic system). The continuous-time chaotic system had already been transformed into discrete-time (DT) chaotic system by Euler method. The phase portrait of DT chaotic system had been implemented on an oscilloscope via Altera field programmable gate array (FPGA) DE2-115. A cryptographic system of RGB image security for 3D chaotic system was proposed. There are three features in the encryption system. First, we use the information of plaintext … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In, 11 Yang and Huang proposed a cryptosystem for color image encryption. On one hand, they proposed a PRNG based on a 3D anti‐control dissipative chaotic system for key generation.…”
Section: Previous Workmentioning
confidence: 99%
“…In, 11 Yang and Huang proposed a cryptosystem for color image encryption. On one hand, they proposed a PRNG based on a 3D anti‐control dissipative chaotic system for key generation.…”
Section: Previous Workmentioning
confidence: 99%
“…Numerous studies based on information and data encryption have been carried out [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Some of these studies have suggested encryption techniques using chaotic system [9, 12, 13, 16-19, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…A novel encryption scheme is suggested in order to cipher the voice data. Differently from the previous studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22] on encryption technique, the algorithm of XOR operation for sequential bits of the pixel has been suggested. In addition, the complement and four bits swapping operations dependent on the number of bits equal to one have also been proposed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Although change-point detection is practical and has been widely used in many fields, it hardly meets real-time detection in the autonomous where need to achieve high-performance. [14][15][16] Hence the hardware implementation of change-point detection is essential. Field-programmable gate array (FPGA) has design flexibility due to its reconfigurable nature and has the advantage of a short design cycle compared with the application-specific integrated circuit (ASIC).…”
Section: Introductionmentioning
confidence: 99%